1999
DOI: 10.1002/1531-8249(199903)45:3<329::aid-ana8>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced lateral premotor activity during paradoxical gait in Parkinson's disease

Abstract: Parkinson's disease (PD) patients often show marked improvement of hypokinetic gait when exposed to special stimuli. To investigate physiological mechanisms underlying this “paradoxical gait” induced by visual cues in PD patients, we examined regional cerebral blood flow changes during gait on a treadmill guided by two different visual cues, the lines oriented transversely to the direction of walk (TL) and the lines parallel to it (PL). Ten PD patients and 10 age‐matched controls received injections of 99mTc‐h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(126 citation statements)
references
References 34 publications
(39 reference statements)
11
110
0
2
Order By: Relevance
“…The authors suggested that utilization of nonaffected brain areas is a compensatory mechanism for basal ganglia dysfunction in movement activation. 33 In our study, we also observed a compensation for the impairment of stride-length regulation under external stimulation via treadmill walking in all patient groups. As in PD, external stimuli could enable the PMC and SMA to better compensate for deficiencies in thalamo-cortical output either caused by antidopaminergic effects of antipsychotic treatment or by a primary pathophysiological condition of schizophrenia.…”
Section: Discussionsupporting
confidence: 72%
“…The authors suggested that utilization of nonaffected brain areas is a compensatory mechanism for basal ganglia dysfunction in movement activation. 33 In our study, we also observed a compensation for the impairment of stride-length regulation under external stimulation via treadmill walking in all patient groups. As in PD, external stimuli could enable the PMC and SMA to better compensate for deficiencies in thalamo-cortical output either caused by antidopaminergic effects of antipsychotic treatment or by a primary pathophysiological condition of schizophrenia.…”
Section: Discussionsupporting
confidence: 72%
“…PMC activation increases in akinetic PD patients relative to controls have been reported earlier (Catalan et al, 1999;Hanakawa et al, 1999;Haslinger et al, 2001;Rascol et al, 1997;Sabatini et al, 2000;Samuel et al, 1997). These studies suggested a compensatory role of the PMC for SMA activation deficits: a feature that we could not detect in this cohort.…”
Section: Correlates Of the Changes In Movement Characteristics Over Timesupporting
confidence: 55%
“…activation paradigms and sequenced unimanual finger movements have also reported increased SMA activation in PD (Jahanshahi et al, 1995), particularly with increasing sequence length and complexity (Catalan et al, 1999). It has subsequently been suggested that lateral premotor (PMC), parietal and cerebellar regions compensate for SMA hypoactivity during parkinsonian movements (Catalan et al, 1999;Hanakawa et al, 1999;Haslinger et al, 2001;Rascol et al, 1997;Sabatini et al, 2000;Samuel et al, 1997). In keeping with the improvement in volitional movements by external cueing in PD, these areas were mainly found to be hyperactive during externally triggered motor tasks.…”
Section: Introductionmentioning
confidence: 90%
“…It is the response to this information which seems to be exaggerated in PD participants. A PET study confirms that PMC mediates locmotor affordance processing, since PMC was more active when participants stepped over transverse lines than lines parallel with the direction of walking (Hanakawa et al, 1999). Importantly, this difference was more pronounced in PD participants than in control participants performing the same step.…”
Section: Implications For Models Of Visually Controlled Walkingmentioning
confidence: 57%